PKM PENERAPAN RUMPON RAMAH LINGKUNGAN BERBASIS MASYARAKAT DI MASA PANDEMI COVID-19 DI KABUPATEN KONAWE SELATAN PROVINSI SULAWESI TENGGARA - La Ode Abdul Rajab Nadia; Salwiyah Salwiyah; Abdullah Abdullah; Amadhan Takwir; Laode Muhamad Hazairin Nadia (Jurnal Marine Kreatif, 2020)
The major problem in fishing production activities faced by fishermen in Wawatu Village is the limited fishing ground area caused by unfriendly-environmentally fishing activities, unorganized spawning and nursery areas so that the availability of fish stocks in their habitats is insufficient for fishermen and traditional fishery businesses. The main focus of this community dedication activity was to further optimize FADs functions as a fishing tool, attracting squid and crabs to gather inside the FADs area. This activity can be one of the solutions to increase fish production during the COVID-19 pandemic in Wawatu Village, North Moramo District, South Konawe Regency. There were two approaches in this activity, namely 1) approach of participatory training to partners, 2) technology applications at the demonstration plot (demplot) location. The result showed that the community was quite enthusiastic in participating in all activities including training and discussion activities as well as the application of environmentally friendly FADs technology, including active participation in material preparation, making of FADs and installing FADs in the water.